Computed tomography in the assessment of pelvic bone fractures in patients with combined injuries - G. Sh. Gasimzade (Сибирский научный медицинский журнал, 2022)
To date, mortality from a complex pelvic injury remains high. It is noted that the total mortality from pelvic injury is 4.7 %. It is recognized that diagnostic imaging plays a leading role in the treatment of pelvic fractures, and image quality helps to reduce the morbidity and mortality of patients with injuries. The aim of the study was to evaluate the role of CT with three-dimensional reconstruction in the diagnosis of pelvic bone fractures. Material and methods. During the 36-month period, 76 patients of both sexes (54 (71.0 %) men and 22 (29.0 %) women) were examined. The Young-Burgess classification system was used to assess the nature of pelvic fractures. A spiral computed tomograph Aquilion 16 Model TSX-101A (Toshiba, Japan) was used. All patients are scanned in a supine position with no movement during the examination. The scan was started from the top of the iliac crest and continued through the level of the sciatic tubercles. The thickness of the cut and the step of the tomography is 10 mm, the table feed is 15 mm per tube revolution, the pitch is 1.5:1, the scanning time is 20–30 seconds. Results. The average age of the patients was 35.2 ± 1.77 years. The largest share was road injuries – 86.9 %: road accidents – 30.3 %, collisions with a pedestrian – 32.9 %, motorcycle and bicycle accidents – 23.7 %, falling from a height – 13.1 % of patients. Pelvic organ radiography diagnosed a sacral fracture in 33 (43.4 %) patients. Anteroposterior compression (AS) was recorded in 9.2 % of cases, of which AS-I in 7.89 %, AS-II – 1.31 %. Lateral compression was observed in 73.68 % of cases: LC-I – 57.89 %, LC-II – 10.53 %, LC-III – 5.26 %. Vertical shift and mixed mechanical injury were detected in 7.89 and in 7.89 % of cases, respectively. The unclassified fracture was detected in 1.31 % of cases. Pelvic ring fractures were associated with sacral fractures (69 (90.8 %) patients) and with acetabular fractures (63 (82.9 %) cases), in 6 (7.9 %) patients – not associated. Conclusions. In combined injuries, lateral compression injuries of the pelvis were more common, which, in comparison with traditional radiographs, were statistically significantly recognized on CT images (p < 0.001), which confirmed the fact that pelvic fractures are more common in lateral compression injuries than in anteroposterior injuries. For a complete assessment of the pelvic ring, in addition to the pelvic view, a CT scan of the lateral part of the sacrum is required.